The complete chloroplast genome and phylogenetic analysis of Smilax moranensis (Liliales: Smilacaceae). Issue 7 (3rd July 2022) - Ji, Baoyu; Pei, Lixin; Cui, Ning
Abstract: Smilax moranensis M.Martens & Galeotti 1842 is an important medicinal plant widely distributed in warm and temperate climates. In this paper, the complete chloroplast (cp) genome of S. moranensis was sequenced using the Illumina platform and assembled for the first time. This plastome is a circular structure of 157, 907 bp in length. The GC content of the plastome was 37.16%. A total of 112 unique genes in this genome have been annotated, including 78 protein-coding genes, 30 transfer RNA genes, and four ribosomal RNA genes. Phylogenetic analysis based on complete cp genome sequences of Smilacaceae family showed that Smilax is monophyletic. The position of S. moranensis was positioned as the sister to the other seven Smilax species. These results provide an important basis for future species identification and taxonomic determinations, as well as the phylogenetic reconstruction of the family Smilacaceae.